Formação de professores de Língua Inglesa: uma proposta antirracista - Francisco, Tadeu Benedito Veiga (2025)
This research, grounded in the Critical Collaborative Research (CCR) methodology and guided by the Collaborative Intention, explores the potential of curriculum deencapsulation of the BNCC (Brazilian National Common Core) through Engaged Multiliteracies as a means to promote anti-racist education among English language students in the upper years of elementary school in Brazil. Addressing the issue of how curricular transformation can foster critical racial awareness among students, this study presents a didactic proposal primarily focused on the anti-racist training of English language teachers. Aiming to use the findings from the research and theoretical foundation to support and shape a future anti-racist training for these educators, the didactic proposal integrates Social Activities and Engaged Multiliteracies, striving to break traditional curricular barriers and promote inclusion. The theoretical framework encompasses the De-encapsulation of the English Language Curriculum, the Pedagogy of Multiliteracies, Engaged Multiliteracies and Social Activities, Anti-racist Education, Teacher Training, Critical Race Theory, Critical Racial Literacy in Education, Racism as Ethical-Political Suffering, and Anti-racist Laws in Brazilian Education. Based on this framework, the study demonstrates racism as an endemic structure upheld by educational and social institutions, incorporating the concept of Ethical-Political Suffering, highlighting the social and emotional impacts of racial exclusion, and aligning with Brazilian anti-racist laws, substantiating the need for transformative educational practices. This research aims to provide teachers with practical strategies to incorporate discussions about structural racism into the English language curriculum, preparing students for more inclusive and conscious engagement with the world. The analysis of this didactic proposal contributes to the discourse on anti-racist education, offering rubrics created by the author based on the theoretical foundation, which serve as tools for teachers to develop their own didactic units, enabling curriculum de-encapsulation in favor of social justice and equity